Reforming Lunar Calendar in Indonesia: The Academic Legacy of Muhammad Basiuni Imran - Wanandi, Zulfian; Suhardiman, Suhardiman; Masuwd, Mowafg Abrahem (Al-Hilal: Journal of Islamic Astronomy, 2025)
This study examines Muhammad Basiuni Imran's views on determining the beginning of the lunar month as outlined in his book entitled Ḥusn al-Jawāb ‘an Itsbāt al-Ahillah bi al-Ḥisāb. He emphasized that differences between rukyat (moon sighting) and ḥisāb (astronomical calculation) should not divide Muslims. Imran argued that using ḥisāb to determine the start of fasting and Islamic holidays is valid in Islam, as it offers a systematic and reliable approach. This library study uses primary and secondary sources, with data collected through interviews and documentation and analyzed using a descriptive-analytical method. The study reveals two key findings. First, Muhammad Basiuni Imran favored ḥisāb over rukyat for determining the lunar month, as it provides greater accuracy, such as precisely locating the crescent and setting prayer times using clocks. Second, his views were shaped by his teachers, including Rashid Rida from Egypt, Ahmad Khatib Al-Minangkabawi, and Shaykh Tahir Jalaluddin, a pioneer of ḥisāb in the Nusantara.